The current status and trends of oral bone regeneration materials: a bibliometric analysis from 1991 to 2023 - Tu, Ronglin; Liu, Xiaoming; Xu, Lin; Yao, Xuemin; Zhang, Ran; Li, Jiadi; Zhang, Wenjun; Liu, Jinrong; Wu, Xiuping; Li, Bing (Frontiers in Materials, 2024)
Objectives: Due to the complexity and importance of oral bone structure, oral bone regeneration materials differ from those used in other parts of the body. To study the research trends and hotspots of oral bone regeneration materials, this paper conducts a bibliometric analysis of related papers from 1991 to 2023 (retrieved on September 27, 2023). Materials and Methods: Using bibliometric methods, two visualization metric software, Citespace and VOSviewer, were used to analyze 1217 papers in SCIE, including paper analysis, author analysis, country and institution analysis, keyword analysis, and cited literature analysis. Results: (1) The number of papers is generally increasing and gradually stabilizing; (2) Buser D is the most influential author, while Jung, Ronald E has the highest number of papers and total citations; (3) The United States has the highest number of papers and citation frequency. The University of Bern and the University of Zurich in Switzerland are not only the institutions with the most papers but also the institutions with the most collaborations with other institutions. (4) Many research directions have persisted for decades since their inception. The field of oral bone regeneration materials is constantly developing and improving. In recent years, the research direction in this field may mainly focus on the role of blood cells and proteins in bone regeneration. (5) In recent years, the types of cited literature mainly include barrier membranes, alveolar ridge augmentation, bone graft materials, histological examination, and in vivo animal experimental models. 非上标/ 下标 设置格式[Ah 辉煌]: Conclusions: The United States and Switzerland have a significant influence in the field of oral bone regeneration materials. The research hotspot in recent years is mainly on tissue engineering materials. However, traditional materials still occupy a large proportion in clinical treatment or research. In addition, the combined use of new and old materials has gradually become one of the research hotspots in this field.